THE INTERNET AND ICT: Opportunities or Threats to the Education World? - Habib Habiburrahim (Universitas Islam Negeri Banda Aceh, 2015)
In this millennium era, the Internet plays pivotal roles in providing educational access. It serves as a significant tool to communicate, discuss, and even explore various information from a different world and reference. In educational world in most developed countries, the Internet is used as an important educational transformation, especially for those who struggle with times and geographical boundaries. As such, the Internet could flexibly bridge between a Professor and a student to communicate and coordinate with regard to their research progress. Beside its advantages, some educational practitioners have harshly criticized the implication of the Internet used in the educational world. Opponents of the Internet users claim that the Internet could threat anyone, including educational world. Oftentimes the Internet is used to do crimes and other unlawful actions, stealing other people's information and money is one of the tangible examples associated with the Internet. Issues on intellectual and copy rights, and other academic misconducts are also connected to the Internet in the last few years. This paper attempts to provide a brief discussion on the advantages and disadvantages of the Internet in higher education.